The сomparison of different approaches to the complex water quality assessment in the small rivers of cities - Veres, Kateryna (WMO, 2006)
Comparison and analysis of water quality integral estimates for small rivers of strongly urbanized territories by different procedures were fixed. Elaboration of advanced procedure was proposed. Such procedure has to take into account the stochastic structure of water quality parameters and their factor conditionality.
Keywords: екологічна оцінка; якість води; екологічна ситуація; малі річки; річковий басейн; урбанізовані території; экологическая оценка; качество воды; экологическая ситуация; малые реки; речные бассейны; урбанизированные территории; ecological appreciation; quality of water; ecological situation; small rivers; river basins; urbanized territories; кафедра туристичного та готельного бізнесу